Multicultural Education in Indonesia: An Alternative for National Education in Global Era - Sutijono, Sutijono (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: Indonesia is still in the process of building its national culture. This is not simple process, considering the fact that there are various ethnic groups with its own characteristics and dynamics. Sometimes, the process causes tensions and conflicts. Furthermore, it is made more complicated by globalization trend which is very expansive in nature. This creates cultural shift which lead to find compromise. Very often this sort intercultural friction gives negative impact. This should carefully addressed by the government by creating a clear policy so that this multi-ethnic and multicultural state has stronger foundation for its existence. One way is by developing a national education which is based on cultural plurality. This paper tries to elaborate the concept and implementation on multicultural education. Due to multicultural approach, education is required to create human resources who is democratic, understanding and respecting differences and cultural and ethnic plurality, and able to keep with the development of science and technology. In the context of teaching and learning, a teacher should have good command of his/her subject matter, good skill of teaching, and good ability to guide learners to get high achievement, in order to develop learners ability and ideal character for the glory of the nation.Key words: Indonesia nation-state, unity in diversity, multicultural education, national education system, and unity in democracy and prosperity.Â About the Author: Drs. Sutijono, M.M. is a Lecturer at the State University of Surabaya (UNESA, Universitas Negeri Surabaya) and currently as a Rector of UNIPA (University of PGRI Adibuana), Jalan Ngagel Dadi III-B/37, Surabaya, East Java, Indonesia. He can be reached at: abdjae@yahoo.co.idHow to cite this article? Sutijono. (2010). âMulticultural Education in Indonesia: An Alternative for National Education in Global Eraâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.1 [Mei], pp.53-66. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (February 1, 2010); Revised (March 4, 2010); and Published (May 20, 2010). Â Â